A study of cutaneous adverse drug reactions in a tertiary care center in south India - Lakshmi Rajendran; Anoop Thyvalappil; Rajiv Sridharan; S Ajayakumar; E M Sparshadeep; Binoo Divakaran (Wolters Kluwer Medknow Publications, 2021)
Background: Cutaneous adverse drug reactions (CADRs) are common among adverse drug reactions (ADRs). Early identification of ADRs can reduce the morbidity and mortality rates. Objectives: To know the pattern of various types of CADRs and to find out the causative drugs involved. Materials and Methods: Retrospective analysis was performed from ADR register, kept in Dermatology department in a tertiary care center. Naranjo's algorithm was used to determine the causality assessment. Details regarding drug intake, morphology of eruption, offending drugs, history regarding hospitalization, drug rechallenge or drug dose modifications, and treatment given to the patients were assessed. The data were subjected to descriptive analysis. Results: A total of 216 patients were recruited into the study, of which 118 were male and 98 were female. Antimicrobials (30.1%) were noted to be the most common offending drugs, followed by antiepileptics (18.1%), analgesics and antipyretics (11.1%), and anticancer drugs (11.1%). The most common presentation of CADR was maculopapular drug eruption (31.5%), followed by fixed drug eruption (13.4%). Conclusion: Among the antimicrobials, penicillins (13.9%) were the most common cause of CADR, followed by cephalosporins (8.8%) and fluoroquinolones (6.9%). A total of 28 patients (13%) were found to have severe cutaneous adverse reactions to drugs. It is important to closely monitor the patient, when a new drug is introduced, which will aid in detecting and preventing of CADRs.